An evaluation of clinical dietitian's perceptions towards telenutrition quality and associated factors. - Eid, Noura; Enani, Sumia; Mosli, Rana H; Shibli, Amal; Baoum, Dalia; Alsulami, Raghad (Journal of King Abdulaziz University: Medical Sciences, 2024)
Background: Telenutrition has been gaining popularity worldwide due to its feasibility and positive impact on improving lifestyle choices and patient outcomes. However, telenutrition approach has not been sufficiently evaluated in Saudi Arabia (SA). Specifically, clinical dietitian’s perceptions and attitudes towards telemedicine in SA is unknown. Objectives: To assess dietitians’ perception on telenutrition quality and examine associations with (sociodemographic characteristics and work experience). Methods: This is a descriptive cross-sectional study, using a translated online survey covering thirty-six-item question study distributed to 300 dietitians working in Saudi Arabia. Questions assessed demographic background and dietitians’ perception and challenges of telenutrition. All Statistical analysis were done using SPSS version 25 using the Kolmogorov–Smirnov test. Results: 108 clinical dietitians; 83% female with a mean age range (25-34) years participated in the study, where the majority of respondents (63%) had experience providing phone and online consultations, with the majority (32.4%) covering referrals for weight loss/weight maintenance. The most common difficulties reported were lack of anthropometric measures (48.1%), followed by technical difficulties (17.6%), and interpersonal or communication difficulties (14.8%). In addition, older age group were the only significant predictor of a higher phone counseling quality score. Conclusion: It is the first study to evaluate dietitians’ perception on the quality of telenutrition in Saudi Arabia. Findings showed promising attitudes towards telenutrition despite its limitations, such as technical errors and absence of nutrition assessment. Yet, the effectiveness and outcomes of telenutrition is still unknown and need further investigation.